Synthesis of New Pyromellitdiimde Homo and Copolymers Containing (N-AllylMethylol) Component - Al-Azzawi , Ahlam Marouf (International Journal of Psychosocial Rehabilitation, 2020)
In this work six new pyromellitdiimde polymers containing (N-allylmethylol) component were synthesized through performing many steps. The first step involved treatment of pyromellitic anhydride with urea producing N-unsubstituted pyromellitdiimide(1) which inturn was converted in the second step to bis(N-methylol) pyromellitdiimide(2) via reaction with formaldehyde. Treatment of (2) with allyl bromide in the third step afforded bis(N-allylmethylol) pyromellitdiimde (3). Subsequently the new monomer (3) was introduced in free radical homo and copolymerization producing the target new polymers (4-9) which exhibit improved properties.